Implementation of a Steam-Based Module Integrating Mathematics Geometry to Cultivate Vocational Values - Kartikasari, Dewi; Basyirun , Basyirun; Sutopo, Yeri; Widjanarko, Dwi (Journal of Vocational and Career Education, 2024)
A teacher’s role involves creating an environment that stimulates and fosters critical thinking skills. One effective approach to promoting vocational values is through integrating mathematics geometry lessons with STEAM-based methods by developing learning modules that serve as independent teaching materials accessible to students. This research aims to design and develop a mathematics geometry learning module for fifth-grade students to instill vocational values. The study follows a Research and Development (R&D) methodology, employing the ADDIE development model. Data collection methods include interviews and questionnaires, analyzed through qualitative and quantitative techniques.The findings demonstrate that the quality of the developed learning module, as validated by five experts; two media specialists from BBPPMPV BOE East Java and three mathematics teachers from Al-YA’LU Excellent Elementary School in Malang meets high standards. Media experts rated the module’s design feasibility with an average score of 3.46, categorized as “highly feasible.” Subject matter experts evaluated the module’s content feasibility with an average score of 3.91 (“highly feasible”), linguistic feasibility at 3.93 (“highly feasible”), and contextual feasibility at 4 (“perfect”).